2013
DOI: 10.1111/aor.12172
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Performance of Chronic Heart Failure Patients in the Early Period of Support by an Axial‐Flow Left Ventricular Assist Device as Destination Therapy

Abstract: Axial-flow left ventricular assist devices (LVADs) are increasingly used as destination therapy in end-stage chronic heart failure (CHF), as they improve survival and quality of life. Their effect on exercise tolerance in the early phase after implantation is still unclear. The aim of this study was to evaluate the effect of LVADs on the exercise capacity of a group of CHF patients within 2 months after initiation of circulatory support. Cardiopulmonary exercise test data were collected for 26 consecutive LVAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…At maximum load, a mean RER of 1.11 (60.07) and a mean lactate concentration of 3.82 (61.0) mmol/L could be measured. Similarly high levels were attained in comparable studies (RER between 1.07 and 1.26 [10,13,[38][39][40]). As the peak exertion level criterion for CPET in healthy subjects, Kroidl et al (16) recommend an RER of >1.11 and an RER of >1.05 in cardiac patients.…”
Section: Cardiopulmonary Exercise Capacitysupporting
confidence: 61%
See 2 more Smart Citations
“…At maximum load, a mean RER of 1.11 (60.07) and a mean lactate concentration of 3.82 (61.0) mmol/L could be measured. Similarly high levels were attained in comparable studies (RER between 1.07 and 1.26 [10,13,[38][39][40]). As the peak exertion level criterion for CPET in healthy subjects, Kroidl et al (16) recommend an RER of >1.11 and an RER of >1.05 in cardiac patients.…”
Section: Cardiopulmonary Exercise Capacitysupporting
confidence: 61%
“…Table 4 summarizes the results of comparable studies which conducted a CPET shortly after LVAD implantation (90 days). In most investigations, comparably low values were recorded (10,13,25,38,39,41 remained unchanged over time at the same (low) levels (12.66 mL/kg/min after 3-6 months, 10.74 mL/kg/min after 1 year, and 11.18 mL/kg/min after more than 1 year). For comparison, patients after heart transplantation usually reach average values of 17-20 mL/kg/min (60-70% of predicted values) in the long term (45).…”
Section: Cardiopulmonary Exercise Capacitymentioning
confidence: 88%
See 1 more Smart Citation
“…These patients are subject to very long periods of hospitalization, because their condition must be stable and they must be able to handle the replacement of external batteries before being discharged to home. These patients have to undergo strict medical supervision and can access the cardiovascular rehabilitation programs; the results of functional recovery are very slow but verifiable [6,[9][10][11]. The patient with L-VAD system is subject to a number of complications both during the hospital stay, and at home, in particular anemia, respiratory problems, recurrent infections in the insertion of the VAD cable, and on rare occasions, thrombosis [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Discharged rotary VAD patients may exhibit slightly improved exercise performance a number of months after implantation compared to unsupported chronic HF patients and are therefore more active [134]. Salamonsen and colleagues found that the larger the pump flow increase in exercise the greater the patient's exercise capacity [135].…”
Section: Exercisementioning
confidence: 99%